Analysis of the Effectiveness of Financial Management on the Implementation of Village-Owned Enterprises (BUMDES) in Gajah District, Demak Regency - yusril baharuddin (Journal of Economic and Business Analysis, 2024)
The effectiveness of BUMDES financial management in Demak Regency, especially in Gajah District, is the focus of this article. Through a qualitative approach and analysis of interviews and literature study, factors that influence the effectiveness of BUMDES financial management were identified. Adoption of clear SOPs, financial management training, and use of financial applications are positive steps. However, challenges such as access to training and resources still need to be overcome. Innovations such as the development of technology-based financial applications, ongoing training, and the implementation of an open financial reporting system are proposed to increase the effectiveness of BUMDES financial management. Support from local governments is key in ensuring the sustainability and success of BUMDES. Suggestions include providing further support in training and resources, optimizing the use of technology, encouraging inter-BUMDES cooperation, and increasing village community participation. By implementing these suggestions, it is hoped that BUMDES financial management can continue to be improved, have a positive impact on the welfare of village communities, and strengthen the role of BUMDES in local economic development. Keywords : BUMDES, Financial Management, Financial Effectiveness.